DOCOSAHEXAENOIC ACID ADMINISTRATION AMELIORATES SCOPOLAMINE-INDUCED MEMORY IMPAIRMENT IN MICE - Saroj, Kothari; Tulika, Singhal (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The main objective of this work was to study the memory-enhancing activity of docosahexaenoic acid (DHA) supplementation in normal memory function and scopolamine-induced impaired memory in mice. Methods: The gum acacia suspension of DHA was administered by gavage at the dose of 200 and 300 mg/kg in mice for 30 days to evaluate memory-enhancing potential on normal and scopolamine-induced impaired memory in albino mice. Escape latency in Morris water maze (MWM) and transfer latency (TL) in elevated plus maze (EPM) were recorded, respectively. Mice were given four trial sessions per day to locate the platform for 4 days in MWM model. Scopolamine 1 mg/kg was injected i.p. to produce memory impairment in mice. Result: DHA suspension at the dose of 300 mg/kg showed significant reduction of escape latency and TL as compared to control group, and the effect was comparable to that of standard nootropic agent piracetam at the dose of 100 mg/kg in normal and scopolamine-treated mice. However, DHA at the dose of 200 mg/kg showed significant memory-enhancing effect in only scopolamine-induced impaired memory model. Conclusion: The study revealed that the chronic administration of DHA exhibited significant memory-enhancing activity against both normal as well as scopolamine-treated impaired memory mice groups, however, this effect was more marked on scopolamine-induced memory impairment as compared to normal memory function.